Barium zirconate titanate-based electronic ceramic and preparation method thereof

By optimizing the chemical composition and preparation process of barium zirconium titanate-based electronic ceramics, the environmental pollution of lead zirconium titanate ceramics and the low Curie temperature of barium zirconium titanate ceramics are solved, and the high voltage electrical performance and high Curie temperature of the ceramics are achieved , suitable for high temperature equipment.

CN119143502BActive Publication Date: 2025-02-11XINXING ELECTRONIC CERAMICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411654581.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-11
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The long-term use of lead zirconium titanate ceramics will cause environmental pollution, and the low Curie temperature of barium zirconium titanate ceramics limits its practical application.

Method used

Using the chemical composition of barium zirconium titanate-based electronic ceramics ((1-α)(BaxCaySm1-x-y)(ZrzTi1-z)O3-αBi(ZnqNb1-q)O3+ metal oxide), the crystal is optimized at the quasi-homotype phase boundary Structure, increase the degree of lattice distortion, and reduce the sintering temperature and refine the grains by adding metal oxides.

Benefits of technology

It improves the piezoelectric properties and Curie temperature of barium zirconium titanate-based electronic ceramics, exceeding 100℃, and is suitable for equipment in high-temperature working environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143502B_ABST
    Figure CN119143502B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electronic ceramic materials, in particular to a barium zirconate titanate-based electronic ceramic and a preparation method thereof, wherein the chemical composition is as follows: (1-α)(Ba x Ca y Sm 1‑x‑y )(Zr z Ti 1‑z )O3‑αBi(Zn q Nb 1‑q )O3+metal oxide, wherein α, x, y, z, and q are atomic percentages; α is 0.05-0.15; x is 0.85-0.95; y is 0.01-0.04; z is 0.1-0.5; q is 0.5-0.8, and the amount of metal oxide is (1-α)(Ba x Ca y Sm 1‑x‑y )(Zr z Ti 1‑z )O3‑αBi(Zn q Nb 1‑q )O3 mass% is 0.1-1%. The barium zirconate titanate-based electronic ceramics prepared by the present invention have good piezoelectric properties and a Curie temperature of more than 100°C, and can be used in equipment in high-temperature working environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electronic ceramic materials, in particular to a barium zirconate titanate-based electronic ceramic and a preparation method thereof. Background Art

[0002] With the rapid development of the electronics industry, the demand for micro energy storage electronic components such as capacitors and integrated circuits is increasing, and higher requirements are also placed on the performance and preparation process of such products. In response to the concept of green, coordinated and sustainable development, environmentally friendly micro energy storage components have become a hot spot for research and development, attracting the attention and research of many scientific researchers at home and abroad, including the electronic ceramic industry, which has a history of decades of development.

[0003] Lead zirconate titanate ceramics have always occupied a dominant position in the field of piezoelectric applications due to their good piezoelectric properties, but the long-term use of lead zirconate titanate ceramics will cause environmental pollution. As people pay more attention to environmental issues, finding new lead-free piezoelectric ceramics to replace lead-containing piezoelectric ceramics has become one of the hot spots in material research. Barium zirconate titanate has attracted widespread attention due to its high dielectric constant, good piezoelectric and ferroelectric properties, but the low Curie temperature seriously limits its practical application. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a barium zirconate titanate-based electronic ceramic and a preparation method thereof. The present invention proposes a barium zirconate titanate-based electronic ceramic and a preparation method thereof. The present invention proposes a barium zirconate titanate-based electronic ceramic and a preparation method thereof.

[0005] The technical solutions adopted are as follows:

[0006] A barium zirconate titanate-based electronic ceramic, the chemical composition of which is as follows:

[0007] (1-α)(Ba x Ca y Sm 1-x-y )(Zr z Ti 1-z )O3-αBi(Zn q Nb 1-q )O3+metal oxide

[0008] Wherein, α, x, y, z, q are atomic percentages;

[0009] α is 0.05-0.15;

[0010] x is 0.85-0.95;

[0011] y is 0.01-0.04;

[0012] z is 0.1-0.5;

[0013] q is 0.5-0.8;

[0014] The amount of metal oxide is (1-α)(Ba x Ca y Sm 1-x-y )(Zr z Ti 1-z )O3-αBi(Zn q Nb 1-q )0.1-1% of the mass of O3.

[0015] Further, α is 0.08-0.12.

[0016] Furthermore, α is 0.1.

[0017] Further, x is 0.88-0.92, y is 0.025-0.035, z is 0.15-0.3, and q is 0.6-0.7.

[0018] Further, x is 0.9, y is 0.03, z is 0.2, and q is 2 / 3.

[0019] Furthermore, the metal oxides include rare earth oxides and transition metal oxides.

[0020] Furthermore, the rare earth oxide is any one or more combinations of Dy2O3, Yb2O3, and Lu2O3.

[0021] Furthermore, the transition metal oxide is any one or more combinations of ZnO, CuO, CoO, FeO and MnO.

[0022] Furthermore, the mass ratio of the rare earth oxide to the transition metal oxide is 1-5:1-5.

[0023] The present invention also provides a method for preparing barium zirconate titanate-based electronic ceramics:

[0024] According to the chemical composition ratio, BaCO3, CaCO3, SmCO3, ZrO2, TiO2, Bi2O3, ZnO and Nb2O5 are weighed, mixed and ball-milled and dried. After pre-sintering at 780-800℃ for 1-3h, metal oxides are added, ball-milled again and dried. Then a binder is added to granulate and dry-pressed. The resulting rough blank is heated to 600-700℃, kept for debinding for 1-4h, then heated to 1300-1400℃, kept for sintering for 2-4h, and then cooled to room temperature in the furnace.

[0025] Beneficial effects of the present invention: The present invention provides a barium zirconate titanate-based electronic ceramic, (1-α)(Ba x Ca y Sm1-x-y )(Zr z Ti 1-z )O3-αBi(Zn q Nb 1-q )O3 has excellent piezoelectric properties because it has a quasi-modular phase boundary (MPB) similar to PZT. The electric domain inside the crystal at the MPB is easily polarized. The more fully polarized, the better the piezoelectric properties will be. In addition, Bi(Zn q Nb 1-q )O3 addition causes the lattice volume to expand, the crystal package parameters to decrease, the lattice distortion to increase, and the change in the lattice structure causes the Curie temperature of the electronic ceramic to rise. The addition of metal oxides can form a certain amount of liquid phase during the sintering process, which can reduce the sintering temperature and refine the grains. At the same time, metal ions enter the ceramic lattice, changing the ceramic crystal structure, and ultimately improving the electrical properties of the electronic ceramic. The barium zirconate titanate-based electronic ceramics prepared by the present invention have good piezoelectric properties and a Curie temperature of more than 100°C, and can be used in equipment in high-temperature working environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a microscopic morphology of the barium zirconate titanate-based electronic ceramic prepared in Example 1. DETAILED DESCRIPTION

[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0028] Embodiment 1:

[0029] A barium zirconate titanate-based electronic ceramic, the chemical composition of which is as follows:

[0030] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )O3+Dy2O3+Yb2O3+CuO

[0031] Among them, the dosage of Dy2O3, Yb2O3 and CuO is respectively

[0032] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )0.1%, 0.1% and 0.2% of the mass of O3.

[0033] The preparation method of the above-mentioned barium zirconate titanate-based electronic ceramics:

[0034] According to the chemical composition ratio, BaCO3, CaCO3, SmCO3, ZrO2, TiO2, Bi2O3, ZnO and Nb2O5 were weighed and added to a planetary ball mill. The mixture was mixed and ball-milled for 10 hours and then dried. The obtained mixed powder was transferred to a muffle furnace and heated to 800°C at a rate of 10°C / min and pre-fired for 2 hours. After returning to room temperature, it was added to a planetary ball mill together with Dy2O3, Yb2O3 and CuO, mixed and ball-milled again for 5 hours and then dried. Polyvinyl alcohol with a mass fraction of 8% was added as a binder for granulation. The obtained pellets were dry-pressed by an oil press at a pressure of 15 MPa. The obtained rough blank was placed in a muffle furnace and heated to 650°C at a rate of 20°C / min, kept warm for 4 hours for debinding, and then heated to 1350°C at a rate of 5°C / min, kept warm for sintering for 2 hours, and then cooled to room temperature.

[0035] Embodiment 2:

[0036] A barium zirconate titanate-based electronic ceramic, the chemical composition of which is as follows:

[0037] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )O3+Yb2O3+CuO

[0038] Among them, the dosage of Yb2O3 and CuO is

[0039] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )0.1% and 0.2% of O3 mass.

[0040] The preparation method of the above-mentioned barium zirconate titanate-based electronic ceramics:

[0041] According to the chemical composition ratio, BaCO3, CaCO3, SmCO3, ZrO2, TiO2, Bi2O3, ZnO and Nb2O5 were weighed and added to a planetary ball mill. The mixture was mixed and ball-milled for 10 hours and then dried. The obtained mixed powder was transferred to a muffle furnace and heated to 800°C at a rate of 10°C / min and pre-fired for 2 hours. After returning to room temperature, it was added to a planetary ball mill together with Yb2O3 and CuO, mixed and ball-milled again for 5 hours and then dried. Polyvinyl alcohol with a mass fraction of 8% was added as a binder for granulation. The obtained pellets were dry-pressed by an oil press at a pressure of 15 MPa. The obtained rough blank was placed in a muffle furnace and heated to 650°C at a rate of 20°C / min, kept warm for 4 hours for debinding, and then heated to 1350°C at a rate of 5°C / min, kept warm for sintering for 2 hours, and then cooled to room temperature.

[0042] Embodiment 3:

[0043] A barium zirconate titanate-based electronic ceramic, the chemical composition of which is as follows:

[0044] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )O3+Lu2O3+CuO

[0045] Among them, the dosage of Lu2O3 and CuO is

[0046] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )0.1% and 0.2% of O3 mass.

[0047] The preparation method of the above-mentioned barium zirconate titanate-based electronic ceramics:

[0048] According to the chemical composition ratio, BaCO3, CaCO3, SmCO3, ZrO2, TiO2, Bi2O3, ZnO and Nb2O5 were weighed and added to a planetary ball mill. The mixture was mixed and ball-milled for 10 hours and then dried. The obtained mixed powder was transferred to a muffle furnace and heated to 800°C at a rate of 10°C / min and pre-fired for 2 hours. After returning to room temperature, it was added to a planetary ball mill together with Lu2O3 and CuO, mixed and ball-milled again for 5 hours and then dried. Polyvinyl alcohol with a mass fraction of 8% was added as a binder for granulation. The obtained pellets were dry-pressed by a hydraulic press at a pressure of 15 MPa. The obtained rough blank was placed in a muffle furnace and heated to 650°C at a rate of 20°C / min, kept warm for 4 hours for debinding, and then heated to 1350°C at a rate of 5°C / min, kept warm for sintering for 2 hours, and then cooled to room temperature.

[0049] Embodiment 4:

[0050] A barium zirconate titanate-based electronic ceramic, the chemical composition of which is as follows:

[0051] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )O3+Dy2O3+CuO

[0052] Among them, the dosage of Dy2O3 and CuO is

[0053] 0.9(Ba 0.9 Ca 0.03 Sm 0.07 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )0.1% and 0.2% of O3 mass.

[0054] The preparation method of the above-mentioned barium zirconate titanate-based electronic ceramics:

[0055] According to the chemical composition ratio, BaCO3, CaCO3, SmCO3, ZrO2, TiO2, Bi2O3, ZnO and Nb2O5 were weighed and added to a planetary ball mill. The mixture was mixed and ball-milled for 10 hours and then dried. The obtained mixed powder was transferred to a muffle furnace and heated to 800°C at a rate of 10°C / min and pre-fired for 2 hours. After returning to room temperature, it was added to a planetary ball mill together with Dy2O3 and CuO, mixed and ball-milled again for 5 hours and then dried. Polyvinyl alcohol with a mass fraction of 8% was added as a binder for granulation. The obtained pellets were dry-pressed by an oil press at a pressure of 15 MPa. The obtained rough blank was placed in a muffle furnace and heated to 650°C at a rate of 20°C / min, kept warm for 4 hours for debinding, and then heated to 1350°C at a rate of 5°C / min, kept warm for sintering for 2 hours, and then cooled to room temperature.

[0056] Comparative Example 1:

[0057] It is basically the same as Example 1, except that Sm doping is not performed;

[0058] A barium zirconate titanate-based electronic ceramic, the chemical composition of which is as follows:

[0059] 0.9(Ba 0.9 Ca 0.1 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )O3+Dy2O3+Yb2O3+CuO

[0060] Among them, the dosage of Lu2O3 and CuO is

[0061] 0.9(Ba 0.9 Ca 0.1 )(Zr 0.2 Ti 0.8 )O3-0.1Bi(Zn 2 / 3 Nb 1 / 3 )0.1% and 0.2% of O3 mass.

[0062] The preparation method of the above-mentioned barium zirconate titanate-based electronic ceramics:

[0063] According to the chemical composition ratio, BaCO3, CaCO3, ZrO2, TiO2, Bi2O3, ZnO and Nb2O5 were weighed and added to a planetary ball mill. The mixture was mixed and ball-milled for 10 hours and then dried. The obtained mixed powder was transferred to a muffle furnace and heated to 800°C at a rate of 10°C / min and pre-fired for 2 hours. After returning to room temperature, it was added to a planetary ball mill together with Dy2O3, Yb2O3 and CuO. The mixture was mixed and ball-milled again for 5 hours and then dried. Polyvinyl alcohol with a mass fraction of 8% was added as a binder for granulation. The obtained pellets were dry-pressed by an oil press at a pressure of 15 MPa. The obtained rough blank was placed in a muffle furnace and heated to 650°C at a rate of 20°C / min, kept warm for 4 hours for debinding, and then heated to 1350°C at a rate of 5°C / min, kept warm for sintering for 2 hours, and then cooled to room temperature.

[0064] Comparative Example 2:

[0065] The same as Example 1, except that Bi(Zn 2 / 3 Nb 1 / 3 )O3.

[0066] Comparative Example 3:

[0067] Basically the same as Example 1, except that Dy2O3 and Yb2O3 are not added.

[0068] Comparative Example 4:

[0069] It is basically the same as Example 1, except that CuO is not added.

[0070] Performance Testing:

[0071] The barium zirconate titanate-based electronic ceramics prepared in Examples 1-4 of the present invention and Comparative Examples 1-4 were polished and uniformly coated with a layer of silver, kept at 100° C. for 5 hours, then heated to 600° C. for 40 minutes, cooled to room temperature, immersed in 100° C. silicone oil and polarized with a 5 kv / mm DC electric field for 40 minutes as samples for performance testing;

[0072] Use ZJ-3A quasi-static d 33 The tester measures the piezoelectric constant of the sample, and uses Agilent's HP4192 precision impedance analyzer to test the resonant frequency, anti-resonant frequency and corresponding impedance of the sample, and calculates the electromechanical coupling coefficient kp and mechanical quality factor Q of the sample. m ;

[0073] According to GB / T 3389.3-2001 "Test Methods for Properties of Piezoelectric Ceramic Materials Curie Temperature T c Test》Test and calculate the Curie temperature of the sample Tc ;

[0074] The test results are shown in Table 1 below:

[0075] It can be seen from Table 1 above that the barium zirconate titanate-based electronic ceramics prepared in the present invention have good piezoelectric properties and a Curie temperature exceeding 100° C., and can be used in equipment in a high-temperature working environment.

[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A barium zirconate titanate-based electronic ceramic, characterized in that: Its chemical composition is as follows: (1-α)(Ba x Ca y Sm 1-x-y )(Zr z Ti 1-z )O3-αBi(Zn q Nb 1-q )O3+metal oxide Wherein, α, x, y, z, q are atomic percentages; α is 0.05-0.15; x is 0.85-0.95; y is 0.01-0.04; z is 0.1-0.5; q is 0.5-0.8; The amount of metal oxide is (1-α)(Ba x Ca y Sm 1-x-y )(Zr z Ti 1-z )O3-αBi(Zn q Nb 1-q )0.1-1% of the mass of O3; The metal oxides include rare earth oxides and transition metal oxides; The rare earth oxide is any one of Dy2O3, Yb2O3, and Lu2O3, or a combination of two or more thereof; The transition metal oxide is CuO; The mass ratio of the rare earth oxide to the transition metal oxide is 1-5:1-5.

2. The barium zirconate titanate-based electronic ceramic according to claim 1, characterized in that: α is 0.08-0.

12.

3. The barium zirconate titanate-based electronic ceramic according to claim 1, characterized in that: α is 0.

1.

4. The barium zirconate titanate-based electronic ceramic according to claim 1, characterized in that: x is 0.88-0.92, y is 0.025-0.035, z is 0.15-0.3, and q is 0.6-0.

7.

5. The barium zirconate titanate-based electronic ceramic according to claim 1, characterized in that: x is 0.9, y is 0.03, z is 0.2, and q is 2 / 3.

6. A method for preparing a barium zirconate titanate-based electronic ceramic according to any one of claims 1 to 5, characterized in that: According to the chemical composition ratio, BaCO3, CaCO3, SmCO3, ZrO2, TiO2, Bi2O3, ZnO and Nb2O5 are weighed, mixed and ball-milled and dried. After pre-sintering at 780-800℃ for 1-3h, metal oxides are added, ball-milled again and dried. Then a binder is added to granulate and dry-pressed. The resulting rough blank is heated to 600-700℃, kept for debinding for 1-4h, then heated to 1300-1400℃, kept for sintering for 2-4h, and then cooled to room temperature in the furnace.

Citation Information

Patent Citations

  • Doped modified barium titanate-based high-pressure porcelain capacitor material

    CN101759433A

  • Calcium barium zirconate titanate based leadless piezoelectric ceramics with low temperature sintering and high piezoelectric properties and preparation method thereof

    CN102351533A